2010
DOI: 10.1007/s10815-010-9412-9
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Can fresh embryo transfers be replaced by cryopreserved-thawed embryo transfers in assisted reproductive cycles? A randomized controlled trial

Abstract: FETs can be performed instead of fresh ETs to improve the outcome of ART in highly selected patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
47
1
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(52 citation statements)
references
References 32 publications
(30 reference statements)
3
47
1
1
Order By: Relevance
“…But as cryopreservation techniques have been refined [8,9], more studies have reported improved outcomes after FET cycles when compared to fresh ET [7,14,15]. Traditionally, embryo cryopreservation was undertaken in patients with surplus embryos or patients with contraindications to transfer such as risk of OHSS or poor endometrial development and in some instances for fertility preservation.…”
Section: Discussionmentioning
confidence: 99%
“…But as cryopreservation techniques have been refined [8,9], more studies have reported improved outcomes after FET cycles when compared to fresh ET [7,14,15]. Traditionally, embryo cryopreservation was undertaken in patients with surplus embryos or patients with contraindications to transfer such as risk of OHSS or poor endometrial development and in some instances for fertility preservation.…”
Section: Discussionmentioning
confidence: 99%
“…Dizygotic twinning was also eliminated in the repeat SET model, whereas the repeat DET model predicted a 20.9 % twin rate with a lower overall live birth rate (39.0 % vs. 41.4 %; [26]). Moreover, there is accumulating evidence that both pregnancy rates [1,27,[30][31][32] and obstetric and neonatal outcomes [11,19] may be improved in cryopreserved cycles, specifically due to uncoupling the processes of COH and embryo transfer. Thus, as routine cryopreservation may emerge as a method to optimize the safety and efficacy of assisted reproduction, the development of prediction models specific to eSET in cryopreserved cycles will become increasingly important, as recently published for fresh embryo transfers [14,36].…”
Section: Discussionmentioning
confidence: 99%
“…However, it is still uncertain whether this strategy might be beneficial for all patients that are submitted to ART treatments [6,16]. A recent meta-analysis showed an increase in ongoing pregnancy rates (OPR) when the freeze-all strategy was performed when compared to fresh embryo transfer [14]; however, there were only three studies included in this meta-analysis [13,17,18]. Furthermore, one of the included studies [17] was retracted due to methodological flaws.…”
Section: Introductionmentioning
confidence: 99%
“…A recent meta-analysis showed an increase in ongoing pregnancy rates (OPR) when the freeze-all strategy was performed when compared to fresh embryo transfer [14]; however, there were only three studies included in this meta-analysis [13,17,18]. Furthermore, one of the included studies [17] was retracted due to methodological flaws. A recent published study evaluated the freeze-all policy in IVF cycles with preimplantation screening (PGS) and also demonstrated benefit in performing elective cryopreservation of all embryos [19].…”
Section: Introductionmentioning
confidence: 99%